Assessment of nutritional status in children using WHO IYCF indicators: an institution based study - Korday, Charusheela S.; Sharma, Ravindra K.; Malik, Sushma (International Journal of Contemporary Pediatrics, 2018)
Background: Poor child feeding practices and sub-optimal breastfeeding have a detrimental effect on health of children less than 2 years of age. We studied the breastfeeding as well as the complementary feeding practices in the children <2 years of age in our tertiary institute with the help of the WHO2008 document, Indicators for assessing infant and young child feeding (IYCF) practices. Methods: This cross-sectional study was carried out in asymptomatic children (< 2 years), in a tertiary care hospital using a pre-designed, validated WHO questionnaire for information regarding feeding practices. Results: The mean age in hours, for initiation of breastfeeding after birth was 3.92. Amongst the age group of 4-5 months, 72.9% (51/70) babies were exclusively breastfed and 86% (43/50) of infants aged 6–8 months received appropriate solid, semi-solid or soft food. Breastfeeding was continued in majority of the children in 90% in the age group of 12-15 months. Only 13 (7.5%) of 177 breastfed babies and only 4 (8.5%) out of 47 non-breastfed were receiving Minimal Acceptable Diet in the 6-23 months group. Conclusions: Although the results for the breastfeeding and weaning indicators were fairly good, there still exists a lack of knowledge about complimentary feeding practices which need to be drastically improved by appropriate health education and dietary advice.